Impact of Climate Change on Potential Planting Areas of Rubber Trees in Yunnan - Lu Weikun; Li Meng; Hu Xueqiong; Li Xiang (应用气象学报)
Based on the meteorological observations since 1981, the impact of climate change on rubber tree planting in Yunnan is analyzed from the aspect of the climatic suitability of rubber tree. The results show that annual average temperature of the main rubber producing counties in the south and east increases by 0.6-0.8℃ in most areas, and more than 1.0℃ in most areas in the west. In January, the average temperature in most areas of the main rubber producing counties in the east of the Ailao Mountain increases by 0-1.0℃, while that in the west increases by 1.0-2.0℃ in the 2010s compared with the 1980s. At the same time, the most suitable and suitable climate area for rubber tree planting increase by 55.3% and 18.6%, respectively. The increased areas are mainly distributed in the west of the Ailao Mountain, indicating that the west area of the Ailao Mountain is more suitable for rubber tree planting due to climate change.